Biodistribution of Liver-Derived Mesenchymal Stem Cells After Peripheral Injection in a Hemophilia A Patient. Issue 8 (August 2017) - Sokal, Etienne M.; Lombard, Catherine Anne; Roelants, Véronique; Najimi, Mustapha; Varma, Sharat; Sargiacomo, Camillo; Ravau, Joachim; Mazza, Giuseppe; Jamar, François; Versavau, Julia; Jacobs, Vanessa; Jacquemin, Marc; et al.
Abstract : Background: With the exception of liver transplantation, there is no cure for hemophilia, which is currently managed by preemptive replacement therapy. Liver-derived stem cells are in clinical development for inborn and acquired liver diseases and could represent a curative treatment for hemophilia A. The liver is a major factor VIII (FVIII) synthesis site, and mesenchymal stem cells have been shown to control joint bleeding in animal models of hemophilia. Adult-derived human liver stem cells (ADHLSCs) have mesenchymal characteristics and have been shown able to engraft in and repopulate both animal and human livers. Thus, the objectives were to evaluate the potency of ADHLSCs to control bleeding in a hemophilia A patient and assess the biodistribution of the cells after intravenous injection. Methods: A patient suffering from hemophilia A was injected with repeated doses of ADHLSCs via a peripheral vein (35 million 111 In-oxine-labeled cells, followed by 125 million cells the next day, and 3 infusions of 250 million cells every 2 weeks thereafter; total infusion period, 50 days). Results: After cell therapy, we found a temporary (15 weeks) decrease in the patient's FVIII requirements and severe bleeding complications, despite a lack of increase in circulating FVIII. The cells were safely administered to the patient via a peripheral vein. Biodistribution analysis revealed an initial temporary entrapment of the cells in the lungs, followed by homing to the liver and to a joint afflicted with hemarthrosis. Conclusion: These results suggest the potential use of ADHLSCs in the treatment of hemophilia A. Abstract : The authors report a case of hemophilia A treated with repeated intravenous injections of adult-derived human liver stem cells that are shown homing to the liver and to a joint affected with hemarthrosis. Supplemental digital content is available in the text.